Germany's uncertain power: foreign policy of the Berlin Republic - Maull, Hanns W. (New perspectives in German studies, 2006)
policy since 1998 / Peter Molt -- Business as usual : Red-Green policies toward Pacific Asia / Jörn-Carsten Gottwald -- Germany and the Iraeli-Palestinian conflict / Martin Beck -- Conclusion : uncertain power - German foreign policy into the twenty-first century / Hanns W. Maull